P16-03. Persistence of robust cross-reactive group M consensus T-cell responses in a chronic HIV-1 clade A1 and D-infected Ugandan population - Serwanga, J.J.; Mugaba, S.; Pimego, E.E.; Lyagoba, F.F.; Nanteza, B.B.; Katongole, E.M.; Ndembi, N.N.; Kaleebu, P.P. (Retrovirology, 2009)
HIV-1 group-M exhibits extraordinary genetic variation, cross-reactivity of immunogens based on consensus clades could be continuously diminishing as the AIDS epidemic progresses. Characterisation of cross-reactive T-cell responses to more central group M consensus peptides in this multi-clade population has not been performed; and could be pertinent for global vaccine
Keywords: High Avidity; Fast Disease Progression; Diverse Virus; Consensus Peptide; Ugandan Population